Uniform Convergence of Cosine Series With Coefficient from New Class of General Monotone - Moch Aruman Imron (Talenta Publisher, 2019)
General monotone sequences class (GMS) has been introduced by Tikhonov. Then Bogdan Szal extended this class to the new class called new class of general monotone. By using non-negative sequence is called ð›½ to controle the difference of sine series coefficient. By substituting ð›½ of modulus of sine series coefficient, we study uniform convergence of new class of general monotone on cosine series.